Comparative transcriptomic analysis provides insights into the regulation of root-specific saponin production in Panax japonicus - Xiangyin Luo; Zhengxiu Ye; Xianming Shi; Ziyao Hu; Junhao Shen; Lei You; Ping Huang; Guodong Wang; Lanlan Zheng; Chen Li; Yonghong Zhang (Scientific Reports)
Abstract Panax japonicus, a traditional medicinal plant from the Araliaceae family, produces bioactive triterpenes with health benefits. In Traditional Chinese Medicine, its roots have been used, but the chemical basis of its medicinal use is unclear, particularly regarding the metabolism and regulation of triterpene saponin biosynthesis. This study employed an integrative approach using Ultra Performance Liquid Chromatography (UPLC) and transcriptome analysis. Our UPLC analysis showed that ginsenoside Ro and chikusetsusaponin IVa were mainly detected in P. japonicus root. Subsequently, a comparative transcriptome analysis of four P. japonicus tissues (roots, leaves, flowers and fruits) was conducted using Illumina sequencing. As a result, 90,985 unigenes were functionally annotated from a total of 211,650 assembled non-redundant transcripts. Among these, 42,829 unigenes were annotated in NR database. Tissue-specific gene analysis revealed that roots had the highest number of specifically expressed unigenes (11,832). The majority of these unigenes were associated with metabolic processes. Additionally, tissue expression patterns analysis for three common transcription factor families indicated that WRKY family genes showed a significantly root-specific expression pattern, potentially playing a role in triterpene saponin biosynthesis. Notably, we investigated the expression profiles of genes related to the biosynthesis of triterpene saponins and found that four genes, ACCT, HMGS, HMGR and SS, encoding key enzymes in triterpene saponins biosynthesis pathway, were primarily expressed in the root. Overall, our study provides a set of P. japonicus tissue transcriptome data, which will aid in the discovery of triterpene saponin biosynthetic genes and offers valuable genetic information for this medical plant.